Pathogenetic substantiation of combination therapy for rosacea - Alexey A. Kubanov; Xenia I. Plakhova; Irina N. Kondrakhina; Sofia V. Volkova (State Scientific Center of Dermatovenereology and Cosmetology, 2023)
Rosacea is a chronic inflammatory dermatosis predominantly damage to the skin of the face, which has a significant negative impact on the quality patients' lives. The main goal of treatment is to achieve the most complete remission. However, due to the fact that the pathogenesis of the disease is not fully understood, the search for new methods of treatment is especially relevant. Combined use pulsed dye laser and ivermectin drug is presented as alternative pathogenetically substantiated method of therapy. The purpose of the study is to characterize immune disorders and the role of cytokines in the pathogenesis of rosacea, as well as the possibilities of combination therapy based on literature data. An analysis of literature sources from the MedLine, Pubmed, eLibrary databases for the period from 2002 to 2022 was carried out, using the keywords "ivermectin", "pulsed dye laser", "rosacea", "cytokines", "ivermectin" , "Pulsed Dye Laser", "rosacea", "cytokines".